Methane emissions from unique wetlands in China case studies, meta analyses, and modelling - Chen, Huai, 1981- (Walter de Gruyter GmbH & Co. KG, in collaboration with Higher Education Press, 2015)
This book provides a systematic basis for understanding CH4 fluxes from unique wetlands of China and their sensitivity to environmental and biotic factors by case studies, meta-analysis and modelling. That is of particular interest to climate managers, policy makers and practicing scientists in different disciplines.